Pemberatan Pidana Terhadap Kasus Marital Rape Ditinjau dari Perspektif Hak Asasi Manusia - Yuwono, Nikmatul Keumala Nofa; Khanif, Al; Triana Ohoiwutun, Y. A. (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2023)
The marital rape case is the one sexual violence case based on unequal relations between husband dan wife. In Indonesia, positive law doesn’t differentiate imprisonment or fines between sexual violence perpetrated by another person and sexual violence perpetrated by a partner in marriage. This article was written using feminist legal theory and human rights which describes the position of women in the eyes of the law and the fulfillment of the rights of wives as victims of marital rape. This study uses a juridical-normative method which aims to explain the criminal burden of rape cases based on a human rights perspective. Conclusion in this study is that cases of marital rape that occurred against wives are a form of violation of human rights in which criminal sanctions are needed to distinguish cases of sexual violence committed by other people from cases of sexual violence committed by partners in marriage.Keywords: Criminal Prosecution, Human Rights, Marital Rape.